Excretion of cysteine and gamma-glutamylcysteine moieties in human and experimental animal gamma-glutamyl transpeptidase deficiency. - Griffith, O W (1980)
Animals treated with potent gamma-glutamyl transpeptidase inhibitors and a patient with severe gamma-glutamyl transpeptidase deficiency excrete much larger than normal amounts of glutathione, gamma-glutamylcysteine, and cysteine in their urine; these compounds were found in disulfide forms. The findings indicate that the metabolic function of gamma-glutamyl transpeptidase is associated with the metabolism or transport (or both) of cysteine, gamma-glutamylcysteine, and glutathione, and that gamma-glutamylcysteine is a physiological substrate of the enzyme. The occurrence of gamma-glutamylcysteine in urine and other considerations suggest that this dipeptide is formed as an extracellular metabolite of glutathione in addition to its recognized role as an intrcellular precursor of glutathione. The dipeptide may be formed by a pathway involving transpeptidation or by cleavage of the Cys-Gly bond of glutathione. In the course of this work it was found that the mixed disulfide between glutathione and gamma-glutamylcysteine is a good substrate of glutathione reductase.